Propolis increases neuronal count in hippocampal area CA1 and prefrontal cortex in stressed rats - Nugroho, Kuswati; Handayani, Ety Sari; Nugraha, Zainuri Sabta (Universa Medicina, 2017)
Background Stress induces neuronal cell damage in the hippocampus and prefrontal cortex. Propolis has a neuroprotective effect that can inhibit apoptosis and decrease neuronal cell count. This study aimed to determine the effect of propolis on neuronal cell count in hippocampal area CA1 and prefrontal cortex in Sprague Dawley rats with induced stress.MethodsA study of laboratory experimental design was conducted involving 24 male Sprague-Dawley Rattus norvegicus. The animals were randomly divided into 4 groups, i.e. controls (K), and stress groups P1, P2 and P3. Controls did not receive treatment, stress group (P1) received stress treatment, groups P2 and P3 received stress and propolis at 100 and 200 mg/kgBW, respectively. Stress and propolis were given for 14 days, followed by termination. The number of neurons in the hippocampal area CA1 and prefrontal cortex were counted. One way ANOVA was used to analyze the data.Results The neuronal count in the hippocampal area CA1 and prefrontal cortex in the stress group (P1) was lower than in groups K, P2 and P3. There were significant differences in the neuronal count of the hippocampal area CA1 between P1 and P3 and P1 and K (p=0.019) and also in the neuronal count of the prefrontal cortex between P1 and P2, P3 and K (p=0.002).Conclusions This study strongly suggest that propolis inhibits the decrease in neuronal count in in the hippocampal area CA1 and prefrontal cortex of Sprague Dawley rats with induced stress. The present study suggests a potential neuroprotective effect of propolis in the prevention of neurodegenerative disorders.